Study of Cyber Security Challenges and Their Impact - Yogesh Rai; Ritu Vishwakarma (International Journal of Wireless Security and Networks, 2024)
In the contemporary digital landscape, the internet has become an indispensable tool for daily activities, encompassing email communication, financial transactions, shopping, reservations, data sharing, and access to information. This interconnected realm, often termed cyberspace, defines our modern era, characterized by the pervasive presence of the Internet of Things (IoT), facilitating ubiquitous data exchange and communication. However, this interconnectedness also exposes vulnerabilities, leading to cybersecurity concerns. The transfer of information traverses numerous systems and networks, introducing risks such as data manipulation and compromised confidentiality. Consequently, a myriad of cybersecurity threats emerge, including online fraud, distributed denial-of-service (DDoS) attacks, phishing attempts, and identity theft. In this study, we aim to delve into the initial stages of these cyber threats, analyzing their implications and ramifications. By examining the evolving landscape of cybersecurity, we seek to foster a deeper understanding of these challenges and explore potential strategies to mitigate their impact effectively.
Keywords: Cyber security; Internet of things (IoT); cybercrime; data sharing; distributed denial-of-service (DDoS) attacks; shopping